The Role of Pancasila in Effort to Preserve Culture, Moral, and Preserve the Youth Generation of Nationalism in the Globalization Era - Ebit, Ebit (Journal of Creativity Student, 2018)
In the era of globalization, we can relate and interact with one another, both with the people around us and the global community easily and very profitably. However, globalization also has a negative impact on the lifestyle of the Indonesian nation, such as the many cultures that enter and cause various problems in this country causing a decrease in the love of culture and nationalism of the younger generation. Indonesian culture can fade and even disappear with time because Indonesian people prefer to imitate foreign cultures. The young generation as the nation's successors must be able to maintain the preservation of their respective regional cultures as proof and identity that we are Indonesians. However, the current phenomenon in our environment is that young people these days feel more proud of foreign cultures. In fact, it is the intentions and enthusiasm of young people who are the key to cultural conservation and the previous generation teaches what they know about the nation's history, traditions, and culture to the younger generation. From an early age, Indonesians must be diligent in learning local languages, regional dances, watching traditional performances or traditional ceremonies, so that their love for culture grows and develops. Now kindergarten children tend to like watching anime and playing with Barbie dolls, all of which are external influences. In the global era, studying foreign cultures, especially mastery of foreign languages (English, Chinese and Arabic) is indeed one of the requirements to get a good job, but that doesn't mean you have to leave the nation's culture. Be proud of the temples, batik, jaipong dance, and drum beats, because this is the identity of the Indonesian people. Our struggle now is to return that love to the younger generation of Indonesia.